Chitinolytic activity of the sheep rumen ciliate Diploplastron affine - Bełzecki, G; Miltko, R; Michałowski, T; Simůnek, J; Kopecný, J (Folia microbiologica, 2008)
Supplementation of the rumen ciliate Diploplastron affine growth medium with commercial chitin stimulated growth of ciliates and the density of their population was positively correlated with chitin doses (r = 0.95; p < 0.01). The cell-free extracts prepared from bacteria-free ciliates degraded chitin to N-acetyl-D: -glucosamine and chitobiose. Three exochitinases, two endochitinases and two beta-N-acetylglucosaminidases were identified in the cell-free extract of protozoa. The molar mass of exochitinases was 80, 65 and 30 kDa, and endochitinases 75 and 50 kDa; the molar mass of one of the identified beta-N-acetylglucosaminidases was 45 kDa.
Keywords: Chitin; kultivační média; Ciliophora; chitinasy; bachor; Sheep; Animals; Rumen; Chitinases; zvířata; protozoální proteiny; Protozoan Proteins; chitin; Culture Media; ovce